2012
DOI: 10.1037/a0024345
|View full text |Cite
|
Sign up to set email alerts
|

Threat of bodily harm has opposing effects on cognition.

Abstract: Several theoretical frameworks have suggested that anxiety/stress impairs cognitive performance. A competing prediction is made by attentional narrowing models that predict that stress decreases the processing of task-irrelevant items, thus benefiting performance when task-irrelevant information interferes with behavior. Critically, previous studies have not evaluated these competing frameworks when potent emotional manipulations are involved. Here, we used threat of bodily harm preceding a color-word Stroop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
62
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 29 publications
12
62
3
1
Order By: Relevance
“…In addition, this task design enabled us to verify that the relatively difficult task design-responding to two tasks at each trial-did not affect the pattern of results. Specifically, we expected that the results of Experiment 2 would be similar to the results of previous experiments that presented emotional stimuli prior to a single (EC) task (Cohen et al, 2011Hu et al, 2012).…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…In addition, this task design enabled us to verify that the relatively difficult task design-responding to two tasks at each trial-did not affect the pattern of results. Specifically, we expected that the results of Experiment 2 would be similar to the results of previous experiments that presented emotional stimuli prior to a single (EC) task (Cohen et al, 2011Hu et al, 2012).…”
mentioning
confidence: 57%
“…Several studies that did examine emotional effect on each of the task conditions found emotional interference-delayed RT following emotional compared to neutral stimuli-for congruent, but not for incongruent stimuli. Namely, RTs for incongruent stimuli appearing after emotional stimuli were found to be similar to RTs for incongruent stimuli appearing after neutral stimuli (Cohen et al, 2011Hu et al, 2012). This effect was suggested to result from diminished emotional response when EC is recruited (Cohen et al, 2011Hu et al, 2012;Kalanthroff, Cohen, & Henik, 2013).…”
mentioning
confidence: 59%
See 3 more Smart Citations